2022
DOI: 10.24874/ti.1025.12.20.04
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Wear Performance of Al-based Composite Reinforced with Al2O3 and MoS2 Using Taguchi Approach

Abstract: The present study is focused on the tribological performance of Molybdenum disulfide (MoS2), and Alumina (Al2O3) used as reinforcement in Al-Si-Mg alloy. By adapting the stir casting route, aluminum matrix composites (AMCs) are manufactured. The process variables such as weight percent of reinforcement i.e., Al2O3 (4,8, 12 and 16 wt. percent ) , and MoS2 (2 and 4 wt. percent), sliding velocity (1 m/s, 1.5 m/s, and 2 m/s), and load (10, 20 and 30 N), on tribological responses are wear rate and coefficient of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…this is because the transfer layer on the composite acts as a protective cover and helps reduce COF. The current result agrees with the study by [45]; COF decreases with load increase. The decrease in COF during sliding wear with an increase in load is due to the accumulation of wear debris in the spaces between the pin and disc, resulting in a reduced adequate depth of penetration, and when the load is exerted, causes the metal surfaces to oxidize more quickly, eventually changing the mechanism from two-body to three-body wear.…”
Section: Analysis and Discussion Of Results Of Cofsupporting
confidence: 93%
“…this is because the transfer layer on the composite acts as a protective cover and helps reduce COF. The current result agrees with the study by [45]; COF decreases with load increase. The decrease in COF during sliding wear with an increase in load is due to the accumulation of wear debris in the spaces between the pin and disc, resulting in a reduced adequate depth of penetration, and when the load is exerted, causes the metal surfaces to oxidize more quickly, eventually changing the mechanism from two-body to three-body wear.…”
Section: Analysis and Discussion Of Results Of Cofsupporting
confidence: 93%
“…The improved hardness of the reinforced samples was also noticed in their work. Vuddagiri and Ravisankar [ 88 ] investigated the tribological behavior of an Al-Si-Mg alloy reinforced with molybdenum disulfide (MoS 2 ) and alumina (Al 2 O 3 ) particles. The resulting composites were manufactured through the stir-casting method.…”
Section: Mechanical and Tribological Properties Of Al-based Mmcsmentioning
confidence: 99%
“…In addition, the tensile strength and hardness of the composites were enhanced with an increase in the Si content [ 89 ]. Furthermore, scanning electron microscope (SEM) examination of the composite surfaces revealed that a combination of abrasive and adhesive wear was the principal wear mechanism at a lower load, while at a higher load, adhesive wear was the predominant mechanism of wear [ 88 ]. Usman et al [ 90 ] fabricated A356 alloy (Al-Si-Mg)-based composites through the stir-casting approach with locust bean waste ash (LBWA) particles as the reinforcement.…”
Section: Mechanical and Tribological Properties Of Al-based Mmcsmentioning
confidence: 99%
“…Vuddagiri et al [11] reported the effect of MoS2 and Al2O3 in tribological behaviour of bearing. Composite manufactured using stir casting process was used in sliding test with sliding velocity and load of 2 m/s and 30N respectively.…”
Section: Introductionmentioning
confidence: 99%